Analysis of Patterns for Settlement of Dispute Rights to Land of Indigenous Law Communities - Ari Dwi Putra; Muhammad Fernanda; Michael Sianturi (Return : Study of Management, Economic and Bussines, 2022)
Backgrounds: Solution Dispute on soil Public law custom conducted through discussion for consensus with each other honor the position of each party that also involves Local Government . aim: for analyze pattern solution dispute right on soil Public law custom Methods: use p approach comparative approach _ this conducted with stage studies comparison law . Findings: Solution disputes that can taken in solution dispute soil ulayat is through discussion for consensus and solution through track law that is lawsuit to State Administrative Court for get certainty law and protection for the parties to the dispute . Cooperation between government and society law custom required in complete dispute right what happened _ so that could give sense of justice for Public law custom procedural law in force in Indonesia